WAYS OF PROVIDING ECOLOGICAL EDUCATION AND ECOLOGICAL EDUCATION BY IMPLEMENTING INTERDISCIPLINARY COMMUNICATION IN TEACHING CHEMISTRY (Conference Zone, 2022)
The formation of competences in the lessons of chemistry and other subjects at school shows the connection between academic subjects.